Cost-effectiveness analysis of benmelstobart, anlotinib, and chemotherapy in extensive-stage small-cell lung cancer - You, Maojin; Luo, Lingling; Lu, Tingting; Chen, Shaofang; He, Ying (Frontiers in Immunology, 2024)
BackgroundThe ETER701 trial assessed the efficacy and safety of benmelstobart combined with anlotinib plus etoposide/cisplatin (BEN-AL-EC) as a first-line therapy for extensive-stage small-cell lung cancer (ES-SCLC). Results indicated that BEN-AL-EC, when compared with placebo in combination with etoposide/cisplatin (PLB-EC), significantly enhanced both progression-free and overall survival rates, while demonstrating an acceptable safety profile among patients with ES-SCLC. However, BEN-AL-EC is expensive, necessitating its cost-effectiveness analysis.MethodsA Markov model with three health states was developed to evaluate the cost-effectiveness of BEN-AL-EC, AL-EC and PLB-EC for the treatment of ES-SCLC from the perspective of the Chinese healthcare system. Drug costs were derived from national tender prices, whereas other costs and utility values were derived from published literature. The key outcomes assessed included total costs, quality-adjusted life years (QALYs), and incremental cost-effectiveness ratios (ICERs). Sensitivity analyses, including one-way and probabilistic analyses, were performed to assess the robustness of the model.ResultsThe total cost of BEN-AL-EC was $55,117.42, yielding 1.09 QALYs, whereas that of PLB-EC was $15,238.15, yielding 0.71 QALYs. The ICER of BEN-AL-EC compared with PLB-EC was $106,249.42 per QALY gained. At a willingness-to-pay threshold of $38,133 per QALY, BEN-AL-EC had a 0% probability of being cost-effective relative to PLB-EC. The key parameters influencing these outcomes included utility values for PFS, the cost of benmelstobart, and the discount rate.ConclusionFrom the perspective of the Chinese healthcare system, BEN-AL-EC as a first-line treatment for ES-SCLC is unlikely to be cost-effective when compared with PLB-EC.